Collective Actions and Territorial Public Policies: the Case of Victims in Medellín - Granada Vahos, James Gilberto; Murcia, Jonathan Alejandro (Universidad del Rosario, 2014)
This paper presents results of the project “Territorial public policy in Medellín, actors, resources and opportunities. The public policies of forced displacement, and sexual and gender diversity”. It proposes a reading of collective actions of the victim population in Medellín, regarding with territorial public policy in attention to victims. So it continues with a research agenda on these two issues and their relationships: the collective actions of the victims and territorial public policies in Medellín and Antioquia. In this text is developed a general context of the public policy of attention to the victims and a little history of the forced displacement policy. Also makes an approach to the collective actions of the victims in the territorial public policy, briefly discusses what happens from national policies to the territories, the relation expressed in the decentralization and territorial approaches. This paper ends with some considerations on the relationship at Medellín between collective action and public policy for the victims of the armed conflict.